Expanding the Discrete Emotions in Physical Education Scale (DEPES): Evaluating Emotions With Behavior and Learning. Issue 1 (2nd January 2023) - Simonton, Kelly L.; Garn, Alex C.; Mercier, Kevin J.
ABSTRACT: Purpose : Students' affective experiences represent essential physical education (PE) learning outcomes. However, measuring these essential internal processes and understanding how they relate to behaviors has been difficult and limited thus far. The purpose of this study was to expand the Discrete Emotions in Physical Education Scale (DEPES) from the original three in-activity emotions (enjoyment, boredom, and anger) to include three additional outcome-related emotions (pride, shame, and relief). Method : Exploratory structural equation modeling (ESEM) analyses investigated the factor structure for the DEPES expansion with middle school (i.e., 6 th, 7 th, & 8 th grade) students from the United States ( N = 495; M age = 11.96 (SD = .98), 57% Female). Additionally, we examined predictive validity with relevant outcomes including perceived social competence, disruptive behavior, and multiple meta-cognitive knowledge beliefs (declarative, conditional, and procedural). Results : ESEM for the six emotions showed good model fit. Standardized factor loadings yielded strong primary loadings with minimal cross loading, suggesting discriminant validity for both in-activity and outcome-related emotions. Also, predictive validity of students' disruptive behavior (21%), social competence (40%), and metacognitive knowledge (40–57%), accounted for a significant portion of knowledge variance. Conclusion : The six emotions measured by the DEPES can provide clear and precise information on students' affective experiences in PE. Furthermore, measuring a variety of discrete emotions can help researchers/teachers capture unique motivational tendencies in students' behavior and knowledge. The evidence speaks to how limiting general positive/negative affect may be when trying to understand students' motivation/behaviors in PE. Overall, the DEPES can make valuable contributions to PE research and practice.